2018
DOI: 10.1017/rdc.2018.69
|View full text |Cite
|
Sign up to set email alerts
|

How Fishy was the Inland Mesolithic? New Data from Friesack, Brandenburg, Germany

Abstract: Recent studies have shown that faunal assemblages from Mesolithic sites in inland Northern Europe contain more fish remains than previously thought, but the archaeological and archaeozoological record does not reveal the dietary importance of aquatic species to hunter-gatherer-fishers, even at a societal level. For example, the function of bone points, as hunting weapons or fishing equipment, has long been debated. Moreover, traditional methods provide no indication of variable subsistence practices within a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…A possible consumption of aquatic food items could lead to a reservoir effect. As a result, the human individuals' chronological ages could be in fact younger, to up to several hundred years, than the apparent age given by the 14 C results, as found in Mesolithic contexts by Meadows et al (2018) and Boethius et al (2017). A review by Fernandes et al (2016) showed a reservoir effect that accounted for a shift of up to 500 years older in radiocarbon ages for Mesolithic and Neolithic human individuals in Europe.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…A possible consumption of aquatic food items could lead to a reservoir effect. As a result, the human individuals' chronological ages could be in fact younger, to up to several hundred years, than the apparent age given by the 14 C results, as found in Mesolithic contexts by Meadows et al (2018) and Boethius et al (2017). A review by Fernandes et al (2016) showed a reservoir effect that accounted for a shift of up to 500 years older in radiocarbon ages for Mesolithic and Neolithic human individuals in Europe.…”
Section: Resultsmentioning
confidence: 84%
“…The fluviatile environment is dominated by peat deposit, and the aquatic ecosystem is highly influenced by terrestrial input and shows relatively low productivity. We thus used the Mesolithic river fishes from Abri du Pape in Belgium (Drucker et al 2018) and Friesack 4 in northern Germany (Meadows et al 2018;Robson pers. comm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The succeeding Late Paleolithic shows a similar pattern in collections from the sites of Monruz, Hauterive-Champréveyres, Henauhof NW level 6 and Henauhof West (Jochim 1998;Leesch et al 2004). It should be noted, however, that recent isotopic studies of human bone from the Mesolithic site of Friesack in northern Germany suggest that some individuals had diets high in fish, even though the faunal collections contain relatively few fish remains (Meadows et al 2018).…”
Section: Archaeology Of Lakeside Sitesmentioning
confidence: 99%
“…A comparison with the site Friesack 4, district Havelland, Brandenburg, shows that in Northern Germany notched or fine-barbed bone points can occur at least up to the late Boreal (Gramsch 1990;/2010. Although no AMS data of directly sampled bone points of this site are available, corresponding finds are proven from the stratified layer complexes I to III of the excavation, which date from the Preboreal to the older Boreal, and from layer complex IV, which spans a time from the late Boreal to the early Atlantic (Gramsch 2009(Gramsch /2010Meadows et al 2018). In this respect, the dating of bone points from Hohen Viecheln should be undisputed.…”
mentioning
confidence: 98%